Application Of Health Belief Model Towards Visual Inspection Behavior Of Acetic Acid In Women Of Reproductive Age As An Effort For Early Detection Of Cervical Cancer - Helen Clondia Siregar; Raisha Octavariny (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Cervical cancer is an uncontrolled growth that occurs in the cervix that begins in the cells that line it to the bottom of the uterus. Most cervical cancers begin in cells in the transformation zone. Objectives: to determine the relationship between the application of the health belief model (perceived susceptibility; perceived severity; perceived threat; perceived benefits; perceived barriers and cues to action) on the behavior of the IVA (Visual Inspection of Acetic Acid) test in women of reproductive age as an effort to detect cervical cancer early.. Research method: quantitative descriptive research with cross sectional method. The study was conducted at UPT Puskesmas Kilometer 11 from December 2023 to February 2024. The population in this study were all women of childbearing age aged 30-50 years totaling 2488 people. By using purposive sampling technique, a sample of 100 respondents was obtained. Results: There is a relationship between Health Belief Model based on Perceived Susceptibility, Perceived Severity, Perceived Threat, Perceived Benefits, Perceived Barriers and Action Cues towards IVA test behavior in Reproductive Age Women as an Effort for Early Detection of Cervical Cancer. Perceived susceptibility is the most dominant variable influencing IVA test behavior in reproductive age women as an effort for early detection of cervical cancer. Conclusion: Dairi District Health Office to increase public understanding of the risk of cervical cancer by providing counseling related to IVA, increasing access to health service facilities by increasing the number of health workers trained in IVA and intensifying mass IVA for sub-districts/wards.